An investigation into the oil transport and starvation of piston ring pack. (January 2019) - Bewsher, SR; Mohammadpour, M; Rahnejat, H; Offner, G; Knaus, O
In order to accurately predict the lubricant film thickness and generated friction in any tribological contact, it is important to determine appropriate boundary conditions, taking into account the oil availability and extent of starvation. This paper presents a two-dimensional hydrodynamic model of a piston ring pack for prediction of lubricant film thickness, friction and total power loss. The model takes into account starvation caused by reverse flow at the conjunctional inlet wedge, and applied to a ring pack, comprising a compression and scraper ring. Inlet boundaries are calculated for an engine cycle of a four-cylinder, four-stroke gasoline engine operating at 1500 r/min with conditions pertaining to the New European Drive Cycle. The analysis shows the two main sources of starvation: first, due to a physical lack of inlet meniscus and second, due to reverse flow at the inlet wedge significantly affecting the prevailing conditions from the generally assumed idealised boundary conditions. Such an approach has not hitherto been reported in literature.